TINGKAT PERSAINGAN BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA TAHUN 2011-2018 - Nonie Afrianty; Mesi Herawati (JURNAL AGHNIYA, 2019)
Abstract The development of the Islamic People's Financing Bank cannot be separated from its role in building the Indonesian economy. Thus, BPRS can increase its competitiveness so that it can survive in the financial institution industry. This study was conducted to analyze the level of competition for BPRS in Indonesia in 2011-2018 at 59 BPRS which were analyzed using the Herfindahl-Hirschman Index (HHI) and Concentration Ratio (CR) methods. The results showed that BPRS in Indonesia had a competition that was not controlled by only a few BPRS or it could be said that the market was perfect competition. Keywords: Competition, BPRS Abstrak Perkembangan Bank Pembiayaan Rakyat Syariah tidak lepas dari perannya dalam membangun perekonomian Indonesia. Dengan demikian, BPRS dapat meningkatkan daya saingnya sehingga dapat bertahan pada industri lembaga keuangan. Penelitian ini dilakukan untuk menganalisis tingkat persaingan BPRS di Indonesia pada tahun 2011-2018 pada 59 BPRS dianalisis dengan metode Herfindahl-Hirschman Index (HHI) dan Concentration Ratio (CR). Hasil penelitian menunjukkan bahwa BPRS di Indonesia memiliki persaingan yang tidak hanya dikuasai oleh beberapa BPRS saja atau dapat dikatakan pasar persaingan sempurna. Kata Kunci: Persaingan, BPRS